Sistema testov dlja ocenki special'noj podgotovlennosti bokserov vysokoj kvalifikacii - Klychko, V.; Savchyn, M. (Science in Olympic Sport, 2019)
The article analyzes the method of determining special fitness level in highly skilled boxers, conditionally divided into two groups: leaders and outsiders.Objective. Determination of objective quantitative criteria of boxers` fitness level for optimization of modeling and fore-casting indices in the system of managing preparation of highly skilled athletes. Methods. Analysis of scientific and methodological literature, chronodynamometry (chronometer "Standard", neuro-chronometer "Diagnostic-ZM", Spuderg-T), testing, methods of mathematical statistics.Results. Based on the use of diagnostic equipment, tests have been developed to assess special fitness of highly skilled boxers. The comparative characteristics of leaders and outsiders (athletes who lost the first fights) have been made. The findings indicate the superiority of leaders over outsiders by 7% (8 s test) and 24-34% test (40 s), respectively. Based on objective quantitative criteria according to the results of long-term testing of the national team of Ukraine members, a four-point scale for evaluation of different aspects of the boxers` fitness was developed, which was used for selection of talented athletes for the national team. Criteria allowing objective evaluation and prediction of the competitive activity efficiency of highly skilled boxers were substantiated. Conclusion. The developed methods allow to measure special fitness level of boxers on the basis of objective quantita-tive indices, thus permitting to increase the efficiency of training process management at the new qualitative level and to objectify the process of selecting talented athletes to perform in competitions.